Clinical Assessment of Risk Management: an INtegrated Approach (CARMINA). Issue 7 (8th August 2016) - Tricarico, Pierfrancesco; Tardivo, Stefano; Sotgiu, Giovanni; Moretti, Francesca; Poletti, Piera; Fiore, Alberto; Monturano, Massimo; Mura, Ida; Privitera, Gaetano; Brusaferro, Silvio
Abstract : Purpose: The European Union recommendations for patient safety calls for shared clinical risk management (CRM) safety standards able to guide organizations in CRM implementation. This project aims to develop a self-evaluation tool to measure healthcare organization performance on CRM and guide improvements over time. Design/methodology/approach: A multistep approach was implemented including: (i) a systematic literature review; (ii) consensus meetings with a expert panel from eight Italian leader organizations to get to an agreement on the first version; (iii) field testing to test instrument feasibility and flexibility; (iv) Delphi strategy with a second expert panel for content validation and balanced scoring system development. Findings: The self-assessment tool - Clinical Assessment of Risk Management: an INtegrated Approach (CARMINA) includes seven areas (governance, communication, knowledge and skills, safe environment, care processes, adverse event management, learning from experience) and 52 standards. Each standard is evaluated according to four performance levels: (i) minimum; (ii) monitoring; (iii) outcomes; (iv) improvement actions, which resulted in a feasible, flexible and valid instrument to be used throughout different organizations. Practical implications: This tool allows practitioners to assess their CRM activities compared to minimum levels, monitor performance, benchmarking with other institutions and spreading results to different stakeholders. Originality/value: The multi-step approach allowed us to identify core minimum CRM levels in a field where no consensus has been reached. Most standards may be easily adopted in other countries.